Being ECR in marine science: Results of a survey among early-career marine scientists and conservationists - Osiecka, Anna N.; Wróbel, Aleksandra; Hendricks, Ida-Wenona; Osiecka-Brzeska, Katarzyna (Frontiers in Marine Science, 2022)
Ocean research and conservation are still largely exclusive fields, with ongoing issues of racial, gender, class, and geographic underrepresentation. To improve accessibility and retention within these fields, we need to create equitable, just, and welcoming study and work environments. It is therefore crucial to listen to the voices of students and early career ocean professionals (ECOP). We conducted an online survey on the study- and workplace experiences of ECOP, focusing on social obstacles, such as economic strain, unpaid work, and workplace discrimination and abuse. Strong economic barriers to education access were evident in certain geographic areas. Almost half of the reported work time in the field was uncompensated, yet unpaid work rarely translated into career advancement and was often associated with workplace abuse. Dissatisfaction and burn-out rates at the earliest career stages were alarming, and experienced hardship and mental health issues were particularly dire for women and non-binary persons. While most respondents were white and from the global north, meaning the results may not reflect experiences of ECOP in other regions, this study highlights some of the barriers to equity as well as work ethics issues that should be urgently addressed within the field.